2015
DOI: 10.1097/inf.0000000000000703
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Rapid and Sensitive Polymerase Chain Reaction Testing in the Emergency Department for Influenza Infections in Children

Abstract: Our model identifies scenarios in which identification of influenza in the emergency department using rapid multiplex PCR testing is a cost-effective strategy for infants and children 3 months through 18 years. Including detection of other respiratory viruses in the analysis would further improve cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 37 publications
2
46
0
Order By: Relevance
“…Lastly, multiplex molecular biology techniques can also be rapidly adapted to detect new or emerging viruses. Although the reagent cost is inherently higher, many studies have clearly demonstrated that appropriately prescribed respiratory multiplex assays are cost-effective and can generate significant savings for hospitals [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, multiplex molecular biology techniques can also be rapidly adapted to detect new or emerging viruses. Although the reagent cost is inherently higher, many studies have clearly demonstrated that appropriately prescribed respiratory multiplex assays are cost-effective and can generate significant savings for hospitals [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining clinical impact of molecular testing among ED patients limit their analysis to analytical sensitivity and specificity comparisons [9]. Additional studies targeting test utilization focus on antiviral prescribing alone [10], overlooking the cascade of management decisions accompanying an influenza diagnosis. Without studies designed to assess the value of ED-based testing within the time frame of the patient encounter, it remains difficult to assess whether RT-PCR testing performed in the ED provides additional value compared to testing performed in centralized hospital laboratories, typically after the ED visit.…”
mentioning
confidence: 99%
“…This may be because physicians did not consider influenza in the differential diagnosis for CAP, were reluctant to treat patients without a positive influenza test (who may be positive for other pathogens), lacked awareness of local influenza circulation, or perceived a lack of antiviral efficacy, particularly when patients present >48 hours from illness onset [23–26]. In addition, not all influenza tests are equal and PCR tests are expensive, leading to barriers to accessing sensitive, specific, and timely influenza tests, which can hinder treatment [27]. Due to low sensitivity and negative predictive value of RIDTs, negative RIDT results alone do not exclude influenza virus infection; antiviral treatment should not be withheld from these patients if influenza is suspected, and further testing with molecular assays is recommended when available, because they have higher sensitivity and specificity [12, 13].…”
Section: Discussionmentioning
confidence: 99%